Prenatal diagnosis of TAPVC on Monday, delivery of Tuesday and cardiac surgery at wednesday - a model of perinatal care in 3rd trimester in case of fetal/neonatal critical heart defect in tertiary center - Respondek-Liberska, Maria; Sokołowski, Łukasz; Słodki, Maciej; Zych-Krekora, Katarzyna; Strzelecka, Iwona; Krekora, Michał; Maroszyńska, Iwona; Moll, Jadwiga; Moll, Jacek (Prenatal Cardiology, 2016)
Total anomalous pulmonary venous connection (TAPVC) is a congenital heart defect (CHD), in which all pulmonary veins connect to the systemic veins or to the right atrium/coronary sinus instead of the left atrium. We present a case report of fetus with prenatally diagnosed isolated infracardiac type of TAPVC in 38th week of gestation. In fetal echocardiographic examination performed in the Department of Prenatal Cardiology, the fetus presented lack of visible pulmonary veins connection to left atrium, abnormal venous confluence behind left atrium, additional vein leading from abdominal cavity to mediastinum and abnormal smooth Doppler blood flow in pulmonary confluence. The accurate prenatal diagnosis allowed to deliver the neonate at term, in tertiary center one day after diagnosis, and to perform surgical reposition of pulmonary veins the following day. The neonate was referred home in a good condition after 28 days of hospitalization. This case is a good example of the value of the 3rd trimester echocardiography.